The Impact of Corruption on Human Rights & the Legal Mechanism for its Compacting: Case of Jordan - Faqir, Raed S. A; Karaki, Muddather Abu; Marashdah, Majed Ahmad K. (Richtmann Publishing, 2011)
The present paper addresses the issue of corruption and human rights in Jordan. This paper aims to explain the concepts ofcorruption and human right, the dimensions of corruption and its types. The main focus of the current study will be on the internationaland national legal frame work to compact corruption, the relation between corruption and economic crimes and organized crimes inJordan. The issue of corruption and a comprehensive development in Jordan will be discussed by this paper. According to the adopted legaland judicial mechanisms to compact corruption in Jordan and the judicial attitude regarding this issue will be highlighted. The currentstudy brings a significant conclusions and recommendations in order to protect human rights from corruptions; it advocates that all theserecommendations are necessary for all branches of the state to reduce and eliminate the phenomena of corruption by all of its types.